Structure-activity relationships of photo-activated soft tissue Adhesive - Wicaksono, Gautama (Nanyang Technological University, 2022)
Soft tissue fixation relies on mechanical means such as sutures, pins, and screws, with potential complications such as concentrated tissue damage, perforation, and the need for secondary surgeries. Using tissue adhesives may reduce these, however soft tissue adhesion remains a challenging problem due to the presence of hydration layer on the tissue surface and the limited availability of covalent bonding sites for the adhesive to adhere onto the tissue. The majority of currently existing soft tissue adhesives relies on click chemistry such as thiol-ene and Schiff base crosslinking, and these are limited by sparse tissue surface concentration of thiol and amines respectively. UV-activated diazirine-based adhesive is proposed by utilizing the photolysis of diazirine into carbene as majority product and diazoalkane as minority product. Carbene allows non-specific crosslinking to covalently bond amino acids, but it competes with hydration layer. Diazoalkane allows specific crosslinking to all available amino acids, but its generation is limited. Herein, the structure-activity relationships of diazirine is investigated by performing real-time rheology during photoactivation. Several strategies of optimizing the usage of diazirine-based adhesive is performed: (1) blending in low-viscosity liquid polymer PCLT to form a solvent-free adhesive, (2) investigation of four different aryl-diazirine precursors to find the optimal carbene-diazoalkane ratio, and (3) optimization of optical properties, i.e. light wavelength, power, and sample thickness and distance. Blending in liquid plasticized polymer to form liquid bioadhesive composite allows tuning of storage modulus of the cured adhesive up to 20 kPa, depending on composition and amount of light exposure. FTIR and NMR analysis of arlydiazirine precursor reveals the decay kinetics of diazoalkane, and in some cases diazoalkane groups are stable for at least 30 minutes. Different UV wavelengths allow curing of diazirine with different efficiency depending on its shift relative to diazirine’s absorbance peak (~360 nm), and the longer wavelengths within this absorption region is able to penetrate the bioadhesive matrix deeper. Finally, to demonstrate potential applications, the proposed CaproGlu bioadhesive is mixed with osseointegrative additive to form a bone cement biocomposite using a model PMMA pin that allows biocomposite curing through a transparent light guide, with resulting lap shear strength up to 40 kPa. Overall, this diazirine-based adhesive system demonstrates a novelty in adhesive design where excellent tunability in material properties can be achieved by modifying composition (adding liquid polymer or solid particles) and light activation parameters (power, wavelength) with direct application towards soft and hard tissue adhesion.